2011
DOI: 10.2174/1874183501104010002
|View full text |Cite
|
Sign up to set email alerts
|

Interface Modification for Tuning the Contact Resistance of Metal/Organic Semiconductor Junctions

Abstract: Abstract:As the performance of organic field-effect transistors improves, the limitation due to charge carrier injection at source and drain electrodes becomes crucial. This review describes the various solutions that have been developed to work around this issue. The most widespread method consists of interposing between the electrodes and the organic semiconductor film a self-assembled monolayer made of an appropriate reactive molecule. In that case, the reduction of the contact resistance may come either fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Although the superior crystalline structure would be the primary factor for explaining the very high hole mobility, the PTAA bottom layer was also shown to be useful for lowering the charge injection barrier by forming the cascade energy structure (Figure S17). 36 The contact resistance estimated by the Y-function method was largely reduced from 2908 Ω cm (for OTFT prepared with homo C 8 -BTBT films) to 1474 Ω cm (for the device with the blend film; Figure S18). 37 Furthermore, the bar-coated devices showed excellent device-to-device uniformity and long-term environmental stability as well.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Although the superior crystalline structure would be the primary factor for explaining the very high hole mobility, the PTAA bottom layer was also shown to be useful for lowering the charge injection barrier by forming the cascade energy structure (Figure S17). 36 The contact resistance estimated by the Y-function method was largely reduced from 2908 Ω cm (for OTFT prepared with homo C 8 -BTBT films) to 1474 Ω cm (for the device with the blend film; Figure S18). 37 Furthermore, the bar-coated devices showed excellent device-to-device uniformity and long-term environmental stability as well.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For this reason, several studies have reported various methodologies for reducing the contact resistance (R c ) between the organic active layer and the source-drain (S-D) electrodes. [12][13][14][15][16][17][18][19][20] The insertion of a thin metal-oxide layer with a high work function (WF) as a hole-injection layer in OFETs has been shown to be an easy and effective way to reduce R c . [21][22][23][24] For example, Kumaki et al have demonstrated that inserting an ultrathin molybdenum oxide (MoO x ) layer in conventional pentacene bottomcontact (BC) transistors could reduce R c by nearly one order of magnitude.…”
mentioning
confidence: 99%
“…If we check the leakage current by making, as previously, a zoom on the starting output characteristics of the OFETs at very low values of the drain-source voltage VDS (Figure 7c and d) Indeed, it is well known that in bottom contact structures, the electrodes engineering is one of the key parameter acting on charge injection into OSC layer. [36,38] In particular, thick electrodes disturb the continuous growth of a single-phase domain in active layer. [39] Moreover, it has also been observed that thick electrodes can also induced high access resistance due to incomplete step coverage at the contact edge.…”
Section: At Very Low Vds the Drain Current Starts From Negative Valumentioning
confidence: 99%
“…This means we need higher gate-source voltage to compensate for the effect of the drain electric field and to get the starting negative drain current. Indeed, it is well known that in bottom contact structures, electrode engineering is one of the key parameters acting on charge injection into the OSC layer [36,37]. In particular, thick electrodes disturb the continuous growth of a single-phase domain in the active layer [38].…”
Section: Evaporated Gold Film As Source and Drain Electrodesmentioning
confidence: 99%